Revealing the Economic Justice in the Inheritance Legal System in Indonesia - Muhammad Majdy Amiruddin (Universitas Islam Negeri Alauddin Makassar, 2022)
The purpose of this study was to reveal economic justice in the inheritance legal system in Indonesia Qualitative research was used in this study to frame, analyze, and provide solutions in the form of a strategic role model for the Indonesian government in completing and streamlining the distribution of inheritance riches. It is hoped that the answers will be based on the difficulties that Islamic groups and religious courts have had in distributing inheritance riches. In addition to zakat, infaq, shodaqoh, and endowments, suggest inheriting money as a public fund. Religious courts and Islamic organizations handle the execution and resolution of inheritance wealth distribution disputes. In Indonesia, the distribution of inherited wealth takes on a new dimension thanks to the proliferation of different types of institutions. Individual family tensions, hoarding treasure, and societal economic inequities could all be avoided if legacy wealth distribution is handled correctly